New imaging features of tuberous sclerosis complex: A 7 T MRI study. (1st June 2021) - Sun, Kaibao; Cui, Jianfei; Xue, Rong; Jiang, Tao; Wang, Bo; Zhang, Zihao; Zhuo, Yan; Zhou, Xiaohong Joe; Liang, Shuli; Yu, Xinguang; Chen, Lin
Abstract : Few in vivo studies have focused on the perivenous association of tubers and iron deposition in the deep gray nuclei in patients with tuberous sclerosis complex (TSC). We investigated this possible relationship in TSC patients using susceptibility weighted imaging (SWI) at 7 T. SWI with high spatial resolution and enhanced sensitivity was performed on 11 TSC patients in comparison with 15 age‐ and sex‐matched healthy controls. The relationship between tubers and veins was evaluated. In addition, the phase images of SWI were processed to produce local field shift (LFS) maps to quantify iron deposition. The mean LFS in the deep gray nuclei was compared between the TSC patients and healthy controls using a covariance analysis. Venous involvement was observed in 211 of the 231 (91.3%) cortical tubers on SWI. The slender tubers often oriented around the long axis of penetrating veins, possibly because cortical tubers typically developed and/or migrated along venous vasculatures. A significant difference in LFS of the thalamus was detected between the TSC patients and healthy controls (3.36 ± 0.50 versus 3.01 ± 0.39, p  < 0.01). The new in vivo imaging features observed at 7 T provide valuable insights into the possible venous association of TSC lesions and iron accumulation in the deep gray nuclei. Our results may lead to a better understanding of the pathological changes involved in TSC under in vivo conditions. Abstract : The new in vivo imaging features observed at 7 T provide valuable insights into the possible venous association of TSC lesions and iron accumulation in the deep gray nuclei. The new imaging features provide new insights for better understanding of TSC.